Satisfaction with service recovery: Its measurement and its outcomes - C. Boshoff; G. Staude (South African Journal of Business Management, 2003)
Persistent poor service delivery will have a harmful impact on the survival and growth prospects of service firms. The literature contends that, if service failures occur, there are strategies that service firms can employ to return customers to a state of satisfaction. Very little scholarly research has been done, however, to assess the satisfaction of customers after service firms have tried to recover from service failure. Although anecdotal evidence suggest it, no empirical research has been done to confirm that effective service recovery will ensure `overall' satisfaction, or the long-term loyalty of complaining customers.The purpose of this study is to assess the validity and reliability of an instrument purported to measure satisfaction with service recovery (RECOVSAT), and to determine which dimensions of service recovery satisfaction are the most important predictors of overall satisfaction and loyalty.
Keywords: 650